Artificial Intelligence dan Kesadaran Kritis Siswa dalam Pembelajaran Sejarah: Analisis Perspektif Paulo Freire - Dilla Sari; Rhoma Dwi Aria Yuliantri (Universitas Hamzanwadi, 2026)
This study aims to identify the forms and patterns of students' AI use in history learning, explore students' perceptions of its benefits and risks, assess students' level of critical consciousness in interacting with AI, and interpret the findings through Paulo Freire's concepts of conscientização, banking education, and dialogical education. This study employed a descriptive qualitative approach with critical interpretation, conducted at SMA Negeri 1 Abung Kunang during the even semester of the 2025/2026 academic year, involving 50 students selected through purposive sampling. Data were collected via Google Form containing Likert-scale closed questions and open-ended questions, then analyzed using simple descriptive statistics and qualitative interpretation based on Freire's perspective. The findings reveal that most students routinely use AI through platforms such as ChatGPT, Gemini AI, and Meta AI to search for information, summarize materials, and complete assignments. While students acknowledge AI's benefits in accelerating comprehension, habits of verifying information and comparing sources remain low. The majority of students fall within the naive consciousness stage in Freire's framework, capable of articulating AI-related risks verbally but unable to translate this awareness into consistent critical behavior. The passive and result-oriented pattern of AI use is identified as reproducing the logic of banking education, while the principles of conscientização and dialogical education have yet to be genuinely realized. This study underscores the necessity of integrating critical AI literacy into history learning to foster students' authentic critical consciousness.